2012
DOI: 10.1091/mbc.e11-12-1003
|View full text |Cite
|
Sign up to set email alerts
|

The PDZ-adaptor protein syntenin-1 regulates HIV-1 entry

Abstract: Syntenin-1 is a cytosolic adaptor protein involved in several cellular processes requiring polarization. Human immunodeficiency virus type 1 (HIV-1) attachment to target CD4+T-cells induces polarization of the viral receptor and coreceptor, CD4/CXCR4, and cellular structures toward the virus contact area, and triggers local actin polymerization and phosphatidylinositol 4,5-bisphosphate (PIP2) production, which are needed for successful HIV infection. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…Furthermore, a spatiotemporal regulatory role for syntenin-1 in actin remodeling has also been documented in CD4 T cells during HIV-1 binding and entry (50). By single-cell force spectroscopy, we have here demonstrated that the interaction with syntenin-1 is strictly dependent on Thr residues in the cytoplasmic tail of ALCAM.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, a spatiotemporal regulatory role for syntenin-1 in actin remodeling has also been documented in CD4 T cells during HIV-1 binding and entry (50). By single-cell force spectroscopy, we have here demonstrated that the interaction with syntenin-1 is strictly dependent on Thr residues in the cytoplasmic tail of ALCAM.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover and considering resting lymphocytes, memory CD4+ T cells appear to be more susceptible to be infected by HIV-1 compared to naïve cells [19], [37][41]. Resting CD4+ T cells represent a major reservoir of HIV-1 [39], [40], being responsible for viremia when antiretroviral therapy is stopped [40].…”
Section: Resultsmentioning
confidence: 99%
“…The dense actin structure that favors CD4/CXCR4 clustering during attachment might subsequently act as a physical barrier that impairs introduction of the viral nucleocapsid. Therefore, a functional but loose actin cytoskeleton seems to be favorable for HIV-1 entry into the host cell (26,57). We have previously reported that silencing syntenin-1, a scaffold protein that binds to the cytoplasmic region of CD4, reduced F-actin polymerization in response to HIV-1 and this promoted HIV-1 entry (57).…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that drebrin also plays a role in HIV-triggered actin polymerization. Reduction of the F-actin structure may render cells more permissive to subsequent HIV-1 nucleocapsid entry, accounting for the negative role of drebrin and syntenin-1 in the HIV-1 entry step (57). Although syntenin-1 silencing increases PIP-2 formation at Env-mediated contacts, drebrin does not.…”
Section: Discussionmentioning
confidence: 99%